Feulgen stain as a special stain for mitotic figures and apoptotic bodies in oral squamous cell carcinoma - Sankari Radhakrishnan; Ramesh Venkatapathy; P D Balamurali; Karthik Shree V Prashad; B Premalatha; Saikat Chakraborty (Wolters Kluwer Medknow Publications, 2018)
Background: Oral cancer is one of the most prevalent cancers worldwide. The oral squamous cell carcinoma (OSCC) is graded for the proper treatment planning, and it has been a subjective phenomenon. This grading depends on several features, of which the presence of mitotic figures and apoptotic bodies is one of the important criteria. The routine hematoxylin and eosin (H and E) staining may help in identifying the mitotic figures and apoptotic bodies, but it is difficult to identify accurately. Thus, an attempt was made to evaluate the efficacy of crystal violet and Feulgen stain in identifying the mitotic figures and apoptotic bodies and to observe any variation in different grades of carcinoma. Aims: This study was aimed at using crystal violet and Feulgen stain in identifying mitotic figures and apoptotic bodies in different grades of OSCC. Materials and Methods: Fifteen diagnosed cases of OSCC were retrieved and stained with routine H and E, crystal violet stain, and Feulgen stain. All the sections were scanned for mitotic figures and apoptotic bodies. Apoptotic index (AI) and mitotic index (MI) were calculated. AI and MI were expressed as the average of a total number of apoptotic and mitotic cells counted in ten high-power fields. Results: A significant increase in MI and AI was found in Feulgen stain than crystal violet and H and E stain. Conclusion: Feulgen stain can be considered as the best, cost-effective, relatively cheap stain to visualize mitotic figures and apoptotic bodies.